An Italy-China Collaboration for Promoting Public Mental Health Recommendations During the COVID-19 Pandemic - Maria Luisa Scattoni; Fabrizio Starace; Fabrizio Starace; Giovanni de Girolamo; Jun Xia (Frontiers Media S.A., 2021)
The rapid evolution of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) emergency involved Italy as the first European country. Meanwhile, China was the only other country to experience the emergency scenario, implementing public health recommendations and raising concerns about the mental health of the population. The Italian National Institute of Health [Istituto Superiore di Sanità (ISS)] reviewed relevant scientific literature in mental health to evaluate the best clinical practices and established the collaboration with the WHO, World Psychiatry Association, and China to support the public health system in a phase of acute emergency. This process permitted the definition of organizational and practical-operational Italian guidelines for the protection of the well-being of healthcare workers. These guidelines have been extensively disseminated within the Italian territory for maximum stakeholder utilization.